Effects of a nursery CO 2 enriched atmosphere on the germination and seedling morphology of two Mediterranean oaks with contrasting leaf habit - Cortés, Pilar; Espelta, J. M.; Save, Robert; Biel, C. (New Forests, 2004)
The use of an enriched CO2 atmosphere in tree nurseries has been envisaged as a promising technique to increase productivity and to obtain seedlings with a higher root/shoot ratio, an essential trait to respond to water stress in Mediterranean-type ecosystems. In that framework, we have analyzed the effects of three levels of atmospheric CO2 concentration (350, 500 and 700 ppm) on the germination rate, growth and morphology of seedlings of two Mediterranean oaks used in reforestation programs: the evergreen Quercus ilex L. and the deciduous Quercus cerrioides Wilk. et Costa. CO2 enrichment increased the germination rate of Q. cerrioides (from 70 7 to 81 3%) while it decreased that of Q. ilex (from 71 10 to 41 12%). Seedlings of both species increased approximately 60% their total biomass in response to CO2 enrichment but at two different CO2 concentrations: 500 ppm for Q. cerrioides and 700 ppm for Q. ilex. This increase in seedlings biomass was entirely due to an augmentation of root biomass. Considering germination and biomass partitioning, an enriched CO2 atmosphere might not be appropriate for growing Mediterranean evergreen oaks, such as Q. ilex, since it reduces acorn germination and the only gains in root biomass occur at a high concentration (700 ppm). On the other hand, a moderate CO2 enrichment (500 ppm) appears as a promising nursery technique to stimulate the germination, growth and root/shoot ratio of deciduous oaks, such as Q. cerrioides
Keywords: Forest restoration; Mediterranean-type ecosystems; Nursery techniques; Quercus cerrioides; Quercus ilex; Wildﬁre

Land use changes, natural regeneration patterns, and restoration practices after a large wildfire in NE Spain: Challenges for fire ecology and landscape restoration - Espelta, J. M.; Rodrigo, A.; Habrouk, A.; Meghelli, N.; Ordonez, J. L.; Retana, J. (FIRE AND BIOLOGICAL PROCESSES, 2002)
Great wildfires have recently affected sub-Mediterranean areas of central Catalonia (NE Spain). The large extension of the burned areas, as well as the fact that non-fire-prone vegetation has been severely affected, lead to ponder over the natural regeneration patterns occurring, and over the best strategies to restore and manage the burned areas. In the present study, we review the land use changes and the natural regeneration patterns observed after the large wildfire that occurred in Bages-Bergueda in 1994. The fire resulted in: (i) the creation of new croplands and pastures in previously forested areas, (ii) the expansion of mixed oak (Quercus ilex and Q. cerrioides) coppices, (iii) the failure of natural regeneration of the dominant tree species (Pinus nigra), leading to the appearance of areas without any tree regeneration. In this context, we discuss the results of different experiments carried out to reforest P nigra stands and to ameliorate the structure of mixed oak coppices.
The following values have no corresponding Zotero field: periodical: FIRE AND BIOLOGICAL PROCESSES pub-location: PO BOX 321, 2300 AH LEIDEN, NETHERLANDS
Keywords: land use changes; Mediterranean areas; natural regeneration; Spain; wildfires

Constraints and trade-offs in Mediterranean plant communities: The case of holm oak-Aleppo pine forests - Zavala, M. A.; Espelta, J. M.; Retana, J. (The Botanical Review, 2000)
In this paper we review those aspects that are relevant to the development of a mechanistic ecological theory to account for the structure and dynamics of Mediterranean forests, focus- ing our attention on mixed forests of holm oak (Quercus ilex L.), a shade-tolerant, slow- growing species that resprouts vigorously after disturbance, and Aleppo pine (Pinus halepen- sis M.), a fast-growing, nonresprouting, shade-intolerant species. The main objectives of this report are: to introduce some of the primary features of these forests, showing their structural complexity and historical peculiarities; to show that much of this complexity can be concep- tually reduced to two main factors of variation, soil-moisture gradients and a complex inter- action of historical management and disturbance regimes; and to contrast the unique features of Mediterranean systems with other communities that have inspired generalization in ecol- ogy. Plants in Mediterranean-climate regions must face several environmental constraints dur- ing their life cycle: water limitation, competition for light, and a complex set of disturbance regimes, mainly fire, herbivory, and human exploitation. The response of co-occurring spe- cies to a given set of environmental constraints depends on a combination of physiological and morphological traits. In holm oak-Aleppo pine forests, the lower limit of distribution along a soil-moisture gradient appears to be controlled by dry-season water stress on seedling performance, and the upper limit seems to be controlled by shade tolerance relative to com- petitors. The processes that generate and maintain these patterns are related to the responses of the two species to the water and light environments that result from interacting gradients of disturbance and resource availability. The dynamics of mixed holm oak-Aleppo pine forests may be represented along two major environmental axes: water availability and light intensity; namely, time since last disturbance. At the regional scale, the presence of holm oak and Aleppo pine is expected to be driven mainly by the precipitation regime, with the proportion of Aleppo pine in- creasing toward the driest border and with holm oak being the dominant species in areas with higher precipitation. Changes of dominance of holm oak and Aleppo pine also re- spond to water availability at the local scale. In this case, variations between species de- pend on different factors in a complex way, because reduced soil-moisture levels may re- sult either from low precipitation or from topography and edaphic features. The dynamics of holm oak-Aleppo pine forests are also determined by temporal changes in canopy clo- sure; that is, forest recovery after disturbance. In this case, the proportion of Aleppo pine would increase in recently disturbed stands (i.e., with high light intensity reaching the for- est floor), whereas regeneration of holm oak would be dominant under partially closed canopies. Theories of forest dynamics developed in humid regions may apply only poorly to Medi- terranean plant communities, where vegetation change is qualitatively or quantitatively dif- ferent. Thus, succession in temperate forests appears to be driven by differences in light availability and shade tolerance; but in Mediterranean plant communities, water limitation is of greater importance for the distribution of forest species. In Mediterranean landscapes the interaction of life-history strategies with changing environments is difficult to infer from observational and experimental studies. A mechanistic approach, in which competi- tion or plant performance is measured as a function of resource availability, seems more feasible. The idea should be to develop multispeeies models calibrated specifically for Mediterranean forests in a combined program of modeling, field research, and experimenta- tion.
Keywords: Aleppo pine; disturbance regimes; forest dynamics; holm oak (voyant); light intensity; mediterranean plant-communities; Water availability

STRUCTURE OF MIXED HOLM-OAK (QUERCUS-ILEX) ALEPPO PINE (PINUS-HALEPENSIS) FORESTS IN NORTHEASTERN SPAIN - Espelta, J. M.; GENE, C.; Retana, J.; TERRADAS, J. (RESPONSES OF FOREST ECOSYSTEMS TO ENVIRONMENTAL CHANGES, 1992)
Mixed forests of Aleppo pine (Pinus halepensis) and holm-oak (Quercus ilex) cover a great part of Northeastern Spain. Nevertheless, little is known about their structure, dynamics and regeneration. For some years, a research group in CREAF has collected data about those aspects, in order to use them to develop models that could be used as a tool for forest management. Previous results obteined about the structure of these stands are presented in the present paper.
The following values have no corresponding Zotero field: periodical: RESPONSES OF FOREST ECOSYSTEMS TO ENVIRONMENTAL CHANGES pub-location: BARKING ESSEX
Keywords: mixed forests; Pinus halepensis; Quercus ilex; Spain